Disruption of BG14 results in enhanced callose deposition in developing seeds and decreases seed longevity and seed dormancy in Arabidopsis. (23rd January 2023) - Wang, Chengliang; Lyu, Yuanyuan; Zhang, Qi; Guo, Hongye; Chen, Defu; Chen, Xiwen
SUMMARY: Seed longevity is an important trait for agriculture and the conservation of genetic resources. β‐1, 3‐Glucanases were first recognized as pathogenesis‐related proteins involved in plant defense, but their roles in seeds are largely unknown. Here, we report a glycosylphosphatidylinositol‐anchored β‐1, 3‐glucanase, BG14, that degrades callose in seed embryos and functions in seed longevity and dormancy in Arabidopsis. The loss of function of BG14 significantly decreased seed longevity, whereas functional reversion (RE) and overexpression (OE) lines reversed and increased the impaired phenotype, respectively. The loss of function of BG14 enhanced callose deposition in the embryos of mature seeds, confirmed by quantitative determination and the decreased callose degrading ability in bg14 . The drop‐and‐see (DANS) assay revealed that the fluorescence signal in bg14 was significantly lower than that observed in the other three genotypes. BG14 is located on the periphery of the cell wall and can completely merge with callose at the plasmodesmata of epidermal cells. BG14 was highly expressed in developing seeds and was induced by aging and abscisic acid (ABA). The loss of function of BG14 led to a variety of phenotypes related to ABA, including reduced seed dormancy and reduced responses to treatment with ABA or pacolblltrazol, whereas OE lines showed the opposite phenotype. The reduced ABA response is because of the decreased level of ABA and the lowered expression of ABA synthesis genes in bg14 . Taken together, this study demonstrated that BG14 is a bona fide BG that mediates callose degradation in the plasmodesmata of embryo cells, transcriptionally influences ABA synthesis genes in developing seeds, and positively affects seed longevity and dormancy in Arabidopsis. Significance Statement: Seed longevity is an important trait for agriculture and genetic resource conservation. β‐1, 3‐Glucanases were first recognized as pathogenesis‐related proteins involved in plant defense, but their roles in seeds are largely unknown. Here, we demonstrated that BG14 is a bona fide BG, mediates callose degradation in the plasmodesmata of embryo cells, transcriptionally influences ABA synthesis genes in developing seeds, and positively affects seed longevity and dormancy in Arabidopsis.